Comment on 'From the Paris Agreement to corporate climate commitments: evaluation of seven methods for setting "science-based" emission targets'. (1st March 2022) - Chang, Andres; Farsan, Alexander; Carrillo Pineda, Alberto; Cummis, Cynthia; Weber, Chris
Abstract: A study from Bjørn et al (2021) suggests that methods to allocate emissions to companies proportionally to their economic growth are consistent with equity-related principles and are effective at conserving a global emissions budget while the science based targets initiative's (SBTi's) absolute contraction approach (ACA) fulfills neither qualification. Here we identify four areas of concern with the study and propose a more comprehensive approach to science based targets (SBT) method evaluation. We respond that first, the authors' method characterization does not differentiate between the emissions allocation that occurs in mitigation scenarios and that which is normatively caused by method formulae, and it misinterprets the drivers of emissions allocation in scenarios. Second, we note that the authors evaluate a method formula for ACA that does not match its use by the SBTi. Third, we acknowledge that allocating emissions based on economic growth can yield incoherent results by comparison to published climate change mitigation scenarios and suggest the authors also evaluate whether methods are effective at conserving sub-global emissions budgets. Fourth, we observe that although the study is framed as an evaluation of SBT methods, it relies almost entirely on assessments of one characteristic. We conclude by proposing a set of principles that should be met by effective SBT methods and a high-level assessment of SBT methods against these principles.